2017
DOI: 10.1142/s0218810417500058
|View full text |Cite
|
Sign up to set email alerts
|

Plate Fixation versus Percutaneous Pinning for Unstable Metacarpal Fractures: A Meta-analysis

Abstract: There is evidence to support the use of pins over ORIF with plates and screws in the treatment of metacarpal fractures. This may have practical advantages, including minimal dissection, easier insertion and availability of the pins. The limitations of this study include the small number of eligible studies, lack of reporting of standard deviation value, and the lack of DASH score assessments at follow up. Further randomized controlled trials that include a larger patient numbers with longer follow up are neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 15 publications
4
30
2
Order By: Relevance
“…However, we did find that patients undergoing closed reduction and percutaneous pin fixation had comparatively higher shortening on radiological assessment compared to those receiving open reduction with internal fixation (ORIF) using plate and screws, and this was most prominent in study subjects younger than 30 years. Our findings are similar to the previous meta-analysis by Melamed et al [9]. The earlier meta-analysis included 5 studies, and our review included 4 additional studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, we did find that patients undergoing closed reduction and percutaneous pin fixation had comparatively higher shortening on radiological assessment compared to those receiving open reduction with internal fixation (ORIF) using plate and screws, and this was most prominent in study subjects younger than 30 years. Our findings are similar to the previous meta-analysis by Melamed et al [9]. The earlier meta-analysis included 5 studies, and our review included 4 additional studies.…”
Section: Discussionsupporting
confidence: 92%
“…However, we have additionally shown that in the longer course (i.e., at > 1 year post-operatively), there are no statistically significant differences in the ROM between the two treatment modalities. The findings that functional scores and grip strength were not significantly different between the two groups corroborated with the findings of the earlier meta-analysis [9].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, a recent meta-analysis conducted by Melamed et al 18 comparing CRPP with K-wires to ORIF with plate and screws for the treatment of unstable metacarpal fractures, focusing on functional outcomes, found statistically significant improved TAM scores with CRPP on their weighted mean analysis of the 3 studies that reported TAM scores. The authors did not find a difference in DASH scores or other functional outcome variables.…”
Section: Discussionmentioning
confidence: 99%